Scallop ceramide 2-aminoethylphosphonate is more effective than egg yolk sphingomyelin in improving cholesterol metabolism in obese/type II diabetic KK-Ay mice - Koki Sugimoto; Ayano Kosaka; Ryota Hosomi; Saki Itonori; Munehiro Yoshida; Kenji Fukunaga (Journal of Functional Foods)
We discovered that the phospholipids present in the internal organs of scallops (Patinopecten yessoensis), which are primarily composed of glycerophospholipids and ceramide 2-aminoethylphosphonate (CAEP), reduced the serum and liver cholesterol contents in mice. This study evaluated the effects of scallop CAEP on lipid metabolism by comparing it to sphingomyelin. The study involved feeding four-week-old male KK-Ay mice either a high-fat diet or a high-fat diet supplemented with 0.5 wt% each of CAEP and sphingomyelin for 35 days. We found that CAEP intake lowered the serum triacylglycerol content, partly via a reduction in the mRNA expression levels of fatty acid synthesis-related genes in the liver. Furthermore, the CAEP diet reduced the serum and liver cholesterol contents. This effect was partially mediated by the increase in fecal total sterol excretion. Thus, this study indicates CAEP will be employed as a health-promoting component to lower the body’s triacylglycerol and cholesterol contents.